Desempenho de Cultivares de Milho Destinados para Produção de Milho Verde e Silagem - Do Couto, Charlismilã Amorim; Da Silva, Érica Munique; Da Silva, Ayure Gomes; Oliveira, Marco Tulio Pimenta; De Vasconcelos, João Carlos; Da Silva, Adelmo Resende; De Albuquerque Sobreira, Elisângela [UNESP]; De Moura, Jadson Bélem (My University, 2017)
Several technologies related to maize (Zea mays L.) are being implemented in Brazil. The use of high genetic potential cultivars along with improved installation conditions and driving culture, are alternatives for better performance. The objective of this research was to evaluate the performance of a group of corn cultivars for the production of corn, silage and grain in Goianésia, Goiás. The design was a randomized blocks, with 37 treatments and three replications. The genotypes were used, from the National Cultivar testing program, coordinated by Embrapa Maize and Sorghum. The plots were composed of a line (3.80 m x 0.80 m). Data were submitted to analysis of variance, being carried out mean comparison by Scott-Knott test (5%). Through the analysis there was a significant effect among cultivars, indicating genetic variability. We conclude that the cultivar CD 324PRO2 highlighted in the results for general characteristics, HTMV1 cultivars AG1051 and AL PIRATININGA for corn characteristics and cultivars CD 324PRO2, AL AVARE and CD 3715PRO for silage characteristics.
Corn cultivars performance intended for production of green corn and silage
Keywords: Agronomic Characteristics; Genotypes (Zea mays L.).; Performance